First-time-right procurement - Munch, Oliver and Ozturen, Ali (2014)
The paper subjects the monetary measurement of purchasing savings to a critical examination and questions whether it still applies. Thus; for example the interaction between purchasing savings and supply chain management (SCM) is investigated. It indicates that monetary purchasing savings exert a negative impact on sustainable company success. It is evident that an alternative to purchasing savings must be found as they are incompatible with the objectives of SCM. In order to achieve a long-term sustainable success, it is proposed that the monetary measurement of purchasing savings be conducted by measuring process times within the procurement organisation.
The paper includes implications for the development of a new way of measuring the performance of procurement comprehensively and in conformity with the sustainable objectives of SCM. It fulfils an identified need to determine whether purchasing savings are compatible with the sustainable approach of SCM and if not, how they could be substituted. The paper is based on a comprehensive literature survey and the findings form the basis for a case study of a German defense company. The study develops a new measurement method, which is not based on monetary factors and supports the objectives of SCM. Because of the case study approach, the research may lack generalizability. Therefore, researchers are encouraged to test the assumptions in order to determine whether the new performance measurement system can be implemented effectively into a procurement organization.
Keywords: Suppy chain management; Purchasing savings